An ontology-based search engine for postgraduate students information at the ministry of higher education portal of Iraq - Abed H.N.; Tang A.Y.C.; Cob Z.C. (IEEE Computer Society, 2023)
In recent times, information integration has gained importance in the provision of focused and structured information for more comprehensive purposes in the educational domain. Although the Ministry of Higher Education in Iraq has a Web portal that provides information pertaining to Postgraduate studies and research, information retrieval supported by the Website still pose a major problem to students. In order to address this problem the researcher in this study propose an ontology based framework for performing the process of information integration in four well-known universities in Iraq. This paper applies Uschold and King ontology building methodology to develop the domain ontology to support information interoperability among the selected Iraqi universities. A query system is then developed for assisting postgraduate students in their search for information related to postgraduate research and development at the universities. © 2013 IEEE.